Effects of rebar on chloride ingress in steel reinforced concrete components - Muthulingam, S.; Rao, B. N. (Journal of Structural Engineering, 2024)
The presence of rebar is of greater importance with respect to chloride ingress into reinforced concrete (RC) structures,as it can influence the spatial distribution of chloride ions to a significant level. The primary objective of this study is to evaluate the non-uniform chloride ingress into concrete, as well as the distribution of chloride around rebar surface, both spatial and temporal variations. The process of chloride ingress into concrete is considered as an interaction between three phenomena, namely: heat transport; moisture transport; and chloride transport. A field equation represents each of these phenomena and subsequent simultaneous numerical solution, using a combined finite element and finite difference scheme, considers their interaction. Further, chloride ingress into RC is investigated by incorporating different parameters such as water-to-binder ratio, concrete cover thickness, and rebar size and location. The spatial and temporal distributions of total chloride content and time-to-corrosion initiation values along the perimeters of rebars not only are considerably affected by rebar sizes and locations but also are non-uniform in nature.